OPTIMASI PRODUKSI WEDANG UWUH SAAT PANDEMI COVID-19 (Studi Kasus di CV. Progress Jogja DIY) - Meisafitri, Nesti; Suprihanti, Antik; Handri Utami, Heni (Journal TECHNO, 2024)
This study aims to analyze optimal combination of inputs, labor, machines and demand for wedang uwuh (original, brewed, and instant) which provides an optimal combination of wedang uwuh production in CV. Progress Jogja. This research uses descriptive method with case study method and the director and production manager as respondents. The types and sources of data are primary and secondary data. Collecting data uses observation, interviews, and documentation method. The data analysis technique uses a Linear Programming (LP). The results showed that there was an optimal combination of input used namely rock sugar, demand for wedang uwuh seduh, and demand for instant wedang uwuh. The combination input such as dry ginger, wet ginger, granulated sugar, nutmeg leaves, sappan wood, clove leaves, labor, machines (cabinet dryer, grinder, grate, spinner, crystallizer) and the demand of original wedang uwuh did not optimal yet